IMPROVING THE UTILIZATION OF TELLERS USING SIMULATION AT XYZ BANK - Saragih, Nova Indah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
Simulation is one of the techniques of operations research and management science that is most used widely. The goal of simulation is to estimate the performance measures of the evaluated system using computers. This paper provides the simulation of tellers to estimate and then improve its performance measure which is the utilization. The initial utilization of XYZ Bank is 24.13% on average. Two scenario are conducted to improve the utilization. Scenario 1 improves the utilization by 32.26% on average and scenario 2 improves the utilization by 47.84% on average. This paper suggests XYZ Bank to apply scenario 2 that can improve the utilization by 23.72%.